The Role of Customer Satisfaction in Forming Trust and Loyalty at Dua Putri Restaurant in Bungku Tengah Morowali - Mohammad Zeylo Auriza; Mahfud Supu; Citra Antasari; Asril; Samuel Aldheony (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The rapid development of the culinary business has made competition in the business world even higher. Starting from small scales such as stalls and angkringan, medium scales such as depots, restaurants and cafes, to large scales such as restaurants in star hotels. The rampant culinary business is often associated with the higher mobility of the community. In addition, it is also often associated with workers or someone who is busy doing activities outside the home, whether it is a woman or a man always looking for something practical in daily fulfillment, especially those related to food. The phenomenon of the proliferation of this culinary business has an impact on Morowali Regency, especially Central Bungku District. One of the most popular restaurants in the Morowali Regency area is the Dua Putri Restaurant. Rumah Makan Dua Putri is oriented towards how all its customers can become loyal customers. By making customers satisfied and trusting when they come to visit the Dua Putri Restaurant. In this study, the research team wanted to measure how the effect of Customer Satisfaction on Customer Trust and Loyalty using the Amos 16.0 software analysis tool. The results of this study indicate that customer satisfaction has a significant effect on customer trust and loyalty at the Dua Putri Restaurant in Morowali Regency.